2005
DOI: 10.1203/01.pdr.0000160591.70409.c8
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Age, Sex and Maternal Parity Correlate with Bone Turnover in Premature Infants

Abstract: Factors affecting bone turnover in premature infants are not entirely clear but certainly are different from those influencing bones of adults and children. To identify fetal and maternal factors that might influence bone turnover, we prospectively studied 50 infants (30 preterm and 20 full-term) born at Ain Shams University Obstetric Hospital in Cairo, Egypt. Maternal parity and medical history and infant's weight, gestational age, gender and anthropometrical measurements were recorded. Cord blood samples wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 22 publications
3
16
0
Order By: Relevance
“…The important role of hip bone shape and geometry in the etiology of hip OA has been established (20). Premature and LBW babies represent a unique vulnerable population, in which bone growth and mineral acquisition are critical in regards to bone turnover (23). A case-control study similarly found reduced peak bone mass at the femoral neck in very LBW babies (3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The important role of hip bone shape and geometry in the etiology of hip OA has been established (20). Premature and LBW babies represent a unique vulnerable population, in which bone growth and mineral acquisition are critical in regards to bone turnover (23). A case-control study similarly found reduced peak bone mass at the femoral neck in very LBW babies (3).…”
Section: Discussionmentioning
confidence: 99%
“…A case-control study similarly found reduced peak bone mass at the femoral neck in very LBW babies (3). There is emerging evidence that preterm birth and very LBW result in a decrease in bone formation and increase in bone resorption (23,24) that reduced osteoclast apoptosis (25) and cartilage degeneration (26), which may be another potential pathway of development of hip OA.…”
Section: Discussionmentioning
confidence: 99%
“…Thus suggesting that birth order do not affect the development of the foetus. Although Aly et al [22] suggested that Parity and maternal diabetes correlated with type 1 procollagen C-terminal propeptide (PICP) which is a bone formation marker; as increase in maternal parity correlated negatively with PICP concentration, but their study did not show a correlation with the developed bony structures. Studies have shown that increase in maternal age increases the chances of Trisomy; diagnosed by foetal nasal bone morphology (nuchal translucency; NT) while decrease in maternal vitamin D level which may be associated with increasing age could affect foetal bone characteristics.…”
Section: Discussionmentioning
confidence: 91%
“…At term, this difference was no longer observable. The gender-difference in serum procollagen type-I carboxy-terminal propeptide may reflect differences in the production of the collagen degradation markers by skeletal and non-skeletal cells in premature infants (Aly, Moustafa, Amer, Hassanein, Keeves, & Patel, 2005). But this difference in BMC was not observed in another study by Namgun, & Tsang, 2000 who stated that gender differences in BMC appear in early life between 1-18 month of age but probably not at birth (Namgung, & Tsang, 2000).…”
Section: Is Caffiene a Risk For Op? 49mentioning
confidence: 94%